AB0248 The impact of therapy on anti-carbamylated protein antibody isotypes and serostatus in patients with early ra treated with abatacept and methotrexate. (15th June 2017) - Trouw, L; Connolly, S; Johnsen, A; Ye, J; Maldonado, M; Toes, R; Huizinga, T
Abstract : Background: Maturation of autoantibody responses has been suggested to be a proxy for disease maturation. Autoantibody responses against post-translationally modified antigens are present in autoimmune diseases and antibodies directed against carbamylated proteins (anti-CarP antibodies) are a marker of RA. Anti-CarP antibody analysis in patients with early RA offers the opportunity to estimate whether specific intervention during such early stages of autoantibody development may have an impact on the maturation of the anti-CarP antibody response. Objectives: We assessed the relationship between changes in anti-CarP isotypes and rates of seroconverson to negative in patients with early RA. Methods: In the Assessing Very Early Rheumatoid arthritis Treatment study (AVERT; NCT01142726 ), patients with early RA were treated with abatacept (ABA)+MTX, ABA monotherapy or MTX alone. 1 Patients in AVERT were anti-cyclic citrullinated peptide-2 positive at baseline for study entry. 1 In this post hoc analysis, concentrations of anti-CarP isotypes were measured using custom ELISAs. Anti-CarP ELISAs for immunoglobulin (Ig)G, IgM or IgA isotypes were performed in patient serum at baseline, and at Days 85 and 365 on treatment. Baseline levels of each anti-CarP antibody isotype and % seropositivity were comparable across the three treatment arms. Adjusted mean change from baseline was calculated using a longitudinal repeated measures model. Results: At baseline, 51.3, 42.5 and 29.3% of all patients with serum available in AVERT were positive for IgG, IgM (indicative of an ongoing immunoresponse) and IgA anti-CarP isotypes, respectively. Overall, approximatly 65% of patients were positive for at least one anti-CarP antibody isotype. Median % change from baseline (25%, 75%) for anti-CarP isotypes levels from baseline to Days 85 and 365 are shown (Table). Analysing patients who were positive at baseline for each of the isotypes, we observed that 19/48 (40%), 16/43 (37%) and 11/48 (23%) of the patients positive for the IgG isotype became negative on ABA+MTX, ABA and MTX, respectively, at 1 year. For the IgM isotype, 26/48 (54%), 14/36 (39%) and 15/38 (39%) became negative on ABA+MTX, ABA and MTX, respectively. For the IgA isotype, 12/26 (46%), 10/23 (43%) and 13/31 (42%) became negative on ABA+MTX, ABA and MTX, respectively. Conclusions: Concentrations of all anti-CarP isotypes (IgM, IgA, IgG) were numerically reduced by abatacept+MTX therapy compared with MTX or abatacept alone. Abatacept+MTX trended towards higher rates of seroconversion to negative for all isotypes over 1 year of treatment. These results indicate that the extent of the anti-CarP antibody response can be modulated by intervention with abatacept on background MTX in anti-citrullinated protein antibody-positive patients with early RA. References: Emery P, et al. Ann Rheum Dis 2015;74:19–26. Disclosure of Interest: L. Trouw: None declared, S. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Johnsen Employee of: Bristol-Myers Squibb, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Toes: None declared, T. Huizinga Grant/research support from: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Bioscience, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Speakers bureau: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough